Eksplorasi Bahasa Indonesia Dalam Gaya Dan Rasa Gastronomi - Rahmah, Adinda Jihan Nur; Fadhillah, Fathia Izzah; Alfath, Keysa Mutiara; Azzahra, Dzikri Millati; Rizkyanfi, Mochamad Whilky (Tourism, Hospitality And Culture Insights Journal, 2024)
This research investigates the study of Indonesian in the context of gastronomy, focusing on the impact of #LaurenceBenson content on knowledge and appreciation of traditional Indonesian cuisine. This research uses a descriptive qualitative method with a literature review and questionnaire-based data collection techniques. The results of the study showed that #LaurenceBenson content was viewed positively by most respondents for introducing and preserving Indonesian culture among foreign and local communities. Positive impacts include increased interest of foreigners in Indonesian cuisine, which can increase the income of Indonesian food businesses and provide new economic opportunities. In this context, knowledge and recognition of diverse local cuisines is very important for Indonesians to present to the international world through media such as #LaurenceBenson content.